Legal Protection of Patient Data Confidentiality Electronic Medical Records - Nabbilah Amir (SOEPRA, 2019)
The use of electronic devices is inseparable from life today, entering the Industrial Revolution era where technological sophistication can replace human tasks, so the use of electronic devices can not only be found in domestic life, offices, and education but also in medical services. The various facilities offered by health care providers both hospitals and clinics in the form of technology utilization are increasingly rapidly becoming one of the electronic medical records that are expected to have a positive impact on reducing paper use. Medical records that used paper (conventional) were changed to electronic medical records. The purpose of this study is to find out and analyze the extent to which electronic medical records can protect the confidentiality of patient data and function as evidence in court in malpractice cases. This study uses normative legal research methods and uses the statute approach method. The results of this study indicate that there needs to be a concern from the government in providing legal certainty regarding the existence of electronic medical records, given that the application has been carried out by several hospitals and clinics in Indonesia. The government should provide standard legal certainty to the changes in conventional medical records to electronic medical records in the form of the issuance of specific laws and regulations regulating electronic medical records.